2020
DOI: 10.5114/ain.2020.95977
|View full text |Cite
|
Sign up to set email alerts
|

Review and analysis of the functionality of mobile applications in the field of alcohol consumption

Abstract: No ghostwriting and guest authorship declared./Nie występują zjawiska ghostwriting i guest authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…W publikacji Wróblewskiego i wsp. [40] wykazano, że z aplikacji prozdrowotnych najpopularniejsze są "trackery", które pozwalają monitorować ilość wypijanego alkoholu, pokazują, ile czasu użytkownik jest w stanie trzeźwości oraz ile porcji alkoholu zostało przyjętych i w jakim czasie. Przegląd literatury autorstwa Wieczorka i Klingemann [41] przedstawia 10 aplikacji mobilnych, dzięki którym użytkownikom udało się ograniczyć dni picia alkoholu.…”
Section: Experts Point Out the Deficits In The Scientificunclassified
See 1 more Smart Citation
“…W publikacji Wróblewskiego i wsp. [40] wykazano, że z aplikacji prozdrowotnych najpopularniejsze są "trackery", które pozwalają monitorować ilość wypijanego alkoholu, pokazują, ile czasu użytkownik jest w stanie trzeźwości oraz ile porcji alkoholu zostało przyjętych i w jakim czasie. Przegląd literatury autorstwa Wieczorka i Klingemann [41] przedstawia 10 aplikacji mobilnych, dzięki którym użytkownikom udało się ograniczyć dni picia alkoholu.…”
Section: Experts Point Out the Deficits In The Scientificunclassified
“…In a publication by Wróblewski et al [40], it was shown that, of the health-promoting apps, the most popular are 'trackers' that allow monitoring the amount of alcohol consumed, showing how long the user has been sober and how many servings of alcohol have been taken and at what time. A literature review by Wieczorek and Klingemann [41] presents 10 mobile apps that have helped users to reduce their drinking days.…”
Section: Experts Point Out the Deficits In The Scientificmentioning
confidence: 99%